TRANSFORMASI DIGITAL ZAKAT: ANALISIS EFEKTIVITAS PLATFORM DIGITAL DALAM PENINGKATAN KEPATUHAN MUZAKKI DI ERA SOCIETY 5.0 - Haryono, Haryono; Yusuf, Rivai (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
The advancement of digital technology in the era of Society 5.0 presents a significant opportunity to optimize zakat management, particularly in enhancing muzaki compliance. This study aims to analyze the effectiveness of digital zakat platforms in encouraging participation and compliance among muzaki in Indonesia. Employing a qualitative approach through case studies of selected national zakat institutions that have adopted digital technologies, data were collected through in-depth interviews, documentation, and participatory observation. Data analysis was conducted using the interactive model of Miles and Huberman. The findings reveal that digital zakat platforms significantly enhance accessibility, transparency, and accountability in zakat management, thereby contributing to increased muzaki compliance—especially among millennials and urban communities. Key features such as zakat calculators, digital reporting, instant payment systems, and reminder notifications serve as the main drivers of improved compliance. However, challenges remain in terms of digital literacy and data security trust. The study concludes that digital transformation of zakat is an effective strategy for modernizing zakat management, provided it is supported by user education, robust digital security systems, and inter-institutional data integration. This study recommends the development of a national digital zakat policy grounded in Sharia principles and adaptive technology.